2020
DOI: 10.3390/cancers12010131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transient Receptor Potential Melastatin 7 (TRPM7) in Cell Viability: A Potential Target to Suppress Breast Cancer Cell Cycle

Abstract: The divalent cation-selective channel transient receptor potential melastatin 7 (TRPM7) channel was shown to affect the proliferation of some types of cancer cell. However, the function of TRPM7 in the viability of breast cancer cells remains unclear. Here we show that TRPM inhibitors suppressed the viability of TRPM7-expressing breast cancer cells. We first demonstrated that the TRPM7 inhibitors 2-aminoethyl diphenylborinate (2-APB), ginsenoside Rd (Gin Rd), and waixenicin A preferentially suppressed the viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 44 publications
0
74
0
Order By: Relevance
“…Recently, TRPM7 has been reported to be implicated in carcinogenesis and has been considered as a potential target for diverse cancer treatment [27,31]. TRPM7, one of the TRP member channels, is permeable to Ca 2+ and Mg 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TRPM7 has been reported to be implicated in carcinogenesis and has been considered as a potential target for diverse cancer treatment [27,31]. TRPM7, one of the TRP member channels, is permeable to Ca 2+ and Mg 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…TRPM7, one of the TRP member channels, is permeable to Ca 2+ and Mg 2+ . Since Ca 2+ is an important regulator of cell cycle and proliferation, TRPM7 regulation is considered to be critical to the biological function of cancer cells [31]. TRPM7 is reported to be overexpressed in human pulmonary adenocarcinoma, and pancreatic and prostate adenocarcinoma [18,32].…”
Section: Discussionmentioning
confidence: 99%
“…To study the dose–response pattern of TRPM7 inhibition, pharmacological inhibition of TRPM7 was performed in conjunction with CRISPR/Cas9-mediated genetic manipulation of TRPM7 using 2-aminoethyl diphenylborinate (2-APB). 2-APB is a general TRP channel blocker that has been shown to inhibit TRPM7 currents in a dose-dependent manner, 25 27 although this inhibitor is not only specific to TRPM7.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the TRPM7 channel serves as a regulator of epithelial-mesenchymal transition (EMT) by meditating signal transducer, and as an activator of transcription 3 (STAT3) phosphorylation as well as vimentin expression. Inhibiting TRPM7 in breast cancer cell lines with 2-APB caused an increment in the percentage of cells in the S phase and a decreased cell population in the G0/G1 phase [49]. In prostate cancer, scientists reported that TRPM7 mediated-Mg 2+ influx promoted the cell migration by inducing EMT, and TRPM7 suppression alleviated TGFβ-induced cell migration with a reduction of EMT markers [50].…”
Section: Intellectual Basementioning
confidence: 99%